2023
DOI: 10.3390/coatings13020456
|View full text |Cite
|
Sign up to set email alerts
|

pH-Sensitive Fluorescence Emission of Boron/Nitrogen Co-Doped Carbon Quantum Dots

Abstract: Carbon quantum dots (CQDs) with their strong photoluminescence (PL) activity, high biocompatibility, robust stability, low cytotoxicity, and flexible surface structures have been employed in many fields including chemical sensing, biosensing, photocatalyst, energy storage, and biomedical applications. Of note, CQDs present an intrinsic pH-sensitive PL nature indicating their intense potential for pH-mediated sensing and imaging. Despite the numerous studies performed in the last two decades, the pH-sensitive P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…The tunable PL emission through manipulating excitation wavelength provides unquestionable opportunities in various applications. So far, many convincing mechanisms such as the quantum confinement effect and surface traps have been proposed to elucidate the excitation‐dependent PL emission [6–8,38–41] . UV‐vis absorption spectra of U‐CQDs (Figure 1b) indicated that various transitions contributed to the final optical characteristics of the material.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The tunable PL emission through manipulating excitation wavelength provides unquestionable opportunities in various applications. So far, many convincing mechanisms such as the quantum confinement effect and surface traps have been proposed to elucidate the excitation‐dependent PL emission [6–8,38–41] . UV‐vis absorption spectra of U‐CQDs (Figure 1b) indicated that various transitions contributed to the final optical characteristics of the material.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in emission intensity with increasing pH can be attributed to the deprotonation of surface groups and resultant aggregation. [8] This phenomenon shows the potential of U/W-CQDs in pH sensor applications including pH monitoring in colloid systems and inside the cell. However, further structural and spectroscopic analyses are required which will be the topic of our perspective work.…”
Section: The Storage and Ph Stability Of U/w-cqdsmentioning
confidence: 89%
See 3 more Smart Citations